The Role of Cybersecurity in Safeguarding Cross-Border E-Commerce and Economic Growth - Kamisetty, Arjun (Asian Business Review, 2024)
This research examines how cybersecurity protects cross-border e-commerce and boosts economic development. With digital commerce growing rapidly, the study examines how strong cybersecurity standards affect customer trust, corporate resilience, and international trade. The research analyzes cybersecurity issues, new technologies, and their economic effects on cross-border e-commerce using secondary data from peer-reviewed journals, industry reports, and regulatory papers. Secure digital platforms are crucial to customer trust, and strong cybersecurity policies may limit financial risks, facilitate corporate innovation, and help SMEs in global marketplaces. Artificial intelligence, blockchain, and sophisticated encryption improve cybersecurity and secure e-commerce platforms. The report also highlights legislative fragmentation and the need for international collaboration to standardize cybersecurity standards. Governments must create collaborative frameworks, encourage firms to embrace cutting-edge security solutions and promote digital literacy to raise consumer awareness. Businesses and governments can build a safe digital trade environment that boosts economic development, minimizes risks, and opens new global commerce possibilities by closing cybersecurity gaps.